Reapresentação das demonstrações contábeis e política de dividendos: evidências no mercado brasileiro - Ballarini, Laise Mascarenhas (2022)
The purpose this paper was to analyze the association between financial restatement and dividend policy in the Brazilian capital market. Using an econometric approach, we analyzed a sample of 275 Brazilian listed companies from 2010-2020. Ours results showed that the firms with higher ROE’s volatility has more probability to restate financial statements. We observe a negative relationship between dividend yields and the financial restatement, which according the hypothesis of the greater information asymmetry is associated with lower dividend distribution. Finally, we founded that there is a positive and significant association between payout and financial Restatement. This results suggests a compensation of dividends retained on the years after financial restatements. In complementary analysis, we observed a dynamic effect of past dividends explain future dividends and restatements have moderate effect with independents variables and dividends. The results have the potential to contribute to managers, auditors, investors, regulators, auditors and members of corporate governance, since with empirical evidence that the restatements of the financial statements are indications of potential information asymmetry and expropriation of shareholders when the manager retains profits without projects with better expected cash flow. In addition, it has the potential to contribute to the assessment of risk and valuation, especially for techniques that we consider dividends with input for the estimation of the firm's value. Also, contribute to reinforce the association of theirs variables to explain the dividend policy.